Strategi Pemasaran Digital: Dampak eWOM di TikTok terhadap Minat Pembelian Skintific - Masithah, Siti Nur; Andriani, Meta (Perhimpunan Sarjana Ekonomi dan Bisnis, 2025)
This study aims to explore the impact of Electronic Word-of-Mouth (eWOM) on consumer purchase intention for Skintific beauty products through the social media platform TikTok. Using the Information Adoption Model (IAM) framework, the study examines independent variables such as information quality, quantity, and credibility; mediating variables including information usefulness and information adoption; and the dependent variable, purchase intention. The research sample consists of active TikTok users interested in beauty-related content and familiar with Skintific products. Data was collected through a survey of 157 respondents and analyzed using a quantitative approach with the Partial Least Squares Structural Equation Modeling (PLS-SEM) method via SmartPLS software. The findings reveal that eWOM on TikTok has a significant impact on purchase intention. Information quality, quantity, and credibility positively influence perceived information usefulness, which in turn enhances information adoption and ultimately drives purchase intention for Skintific products. This research provides practical insights for digital marketing strategies, especially in rapidly evolving social media platforms like TikTok. Additionally, the findings serve as a reference for marketers to effectively leverage eWOM in influencing consumer purchase decisions.